Low-dimensional nanomaterial peeling method using liquid crystal, liquid crystal-low-dimensional nanomaterial composite manufacturing method using the same
Patent Information
- Application Number
- KR1020240059676
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-01-17
- Filing Date
- 2024-05-07
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2044-05-07
Smart Images

Figure 112024049121850-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for exfoliating nanomaterials, and more specifically, to a method for exfoliating low-dimensional nanomaterials using a liquid crystal material. Background Technology
[0002] Low-dimensional materials are materials that are widely found in nature. Examples of such low-dimensional materials include two-dimensional layered materials such as graphene, transition metal dichalcogenides, and MXene, as well as one-dimensional materials such as carbon nanotubes.
[0003] Various techniques have been developed to exfoliate existing low-dimensional nanomaterials from bulk into thin layers, and these exfoliated materials can be usefully employed in the electronics field due to their diverse properties.
[0004] Liquid exfoliation is a defoliation technique that takes place in a solution and is known as a highly efficient method utilizing metal intercalation; however, since defoliation occurs under high voltage and high vacuum conditions and it is difficult to completely remove residual metal ions, there is a problem in that the final composite material contains ionic impurities.
[0005] In particular, when exfoliating MoS2, a two-dimensional nanomaterial, using liquid exfoliation results in the problem of exfoliation into an unstable 1T (conductor) phase rather than a stable 2H (semiconductor) phase.
[0006] In addition, existing exfoliation methods often had very low dispersion stability and concentration, and especially in the case of high dispersion of MoS2, it was difficult to apply to specific fields such as polymer synthesis because highly toxic solvents with a boiling point of 200°C or higher were commonly used. Prior art literature
[0007] Republic of Korea Published Patent Application 10-2023-0095139 The problem to be solved
[0008] The present invention provides a method for exfoliating low-dimensional nanomaterials that uses a liquid crystal material to solve the problems of the aforementioned prior art, enabling simultaneous exfoliation and dispersion of low-dimensional materials, and achieving high dispersion stability and exfoliation concentration.
[0009] The technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art to which the present invention belongs from the description below. means of solving the problem
[0010] To achieve the above technical problem, one embodiment of the present invention provides a method for exfoliating low-dimensional nanomaterials.
[0011] A method for exfoliating a low-dimensional nanomaterial according to one embodiment of the present invention is characterized by comprising the steps of: mixing a low-dimensional nanomaterial bulk powder with a liquid crystal material to form a mixture; heating the mixture under a temperature condition of 70°C to 150°C; adding a solvent to the mixture to form a solution; and applying ultrasound to the solution.
[0012] In an embodiment of the present invention, the low-dimensional nanomaterial may be a method for exfoliating a low-dimensional nanomaterial characterized in that the low-dimensional nanomaterial is graphene, carbon nanotubes, transition metal dichalcogenogen compounds, TiC, or hBN.
[0013] In an embodiment of the present invention, the liquid crystal material may be a low-dimensional nanomaterial exfoliation method characterized by comprising a liquid crystal molecule containing a benzoate functional group.
[0014] In an embodiment of the present invention, the step of forming the mixture may be a method for exfoliating a low-dimensional nanomaterial, characterized by physically crushing the low-dimensional nanomaterial bulk powder and then mixing it with a liquid crystal material.
[0015] In an embodiment of the present invention, the heat treatment step may be a method for exfoliating low-dimensional nanomaterials characterized by being performed for 6 to 24 hours.
[0016] In an embodiment of the present invention, the heat treatment step may be a method for exfoliating low-dimensional nanomaterials characterized by being performed under a temperature condition of 125°C to 140°C.
[0017] In an embodiment of the present invention, the solvent may be a low-dimensional nanomaterial exfoliation method characterized by being tetrahydrofuran or N-methylpyrrolidone.
[0018] Another embodiment of the present invention for achieving the above technical problem provides a method for manufacturing a liquid crystal-low-dimensional nanomaterial composite.
[0019] A method for manufacturing a liquid crystal-low-dimensional nanomaterial composite according to one embodiment of the present invention is characterized by comprising: a step of separating a low-dimensional nanomaterial bulk powder from the solution after a step of applying ultrasound to the solution; and a step of drying the solution.
[0020] Another embodiment of the present invention for achieving the above technical problem provides a liquid crystal-low-dimensional nanomaterial composite manufactured by the method for manufacturing the liquid crystal-low-dimensional nanomaterial composite. Effects of the invention
[0021] According to an embodiment of the present invention, a manufacturing method having a simplified process is provided, which eliminates the need for a nitrogen atmosphere or vacuum conditions required in conventional processes and enables high-concentration peeling even under atmospheric conditions, and reduces the conventional two-step process, which involves peeling followed by a dispersion process using a liquid crystal material as a peeling agent / dispersing agent, into a one-step process where peeling and dispersion can be performed simultaneously.
[0022] Specifically, due to the simplified process, economic feasibility is ensured, mass production becomes possible, nanomaterials can be dispersed at a high concentration on the liquid crystal, and a dispersion solution with excellent dispersion stability can be obtained.
[0023] Furthermore, according to an embodiment of the present invention, the liquid crystal-low-dimensional nanomaterial composite prepared by drying the solution is expected to possess anisotropic mechanical, optical, and electrical properties because the liquid crystals are aligned in a specific direction by an electric field, magnetic field, or mechanical stress. Therefore, the prepared composite has the effect of being usable in various applications, such as high-strength composite materials, heat dissipation materials for thermal control, polarizing films for light control, electronic devices, and energy devices.
[0024] The effects of the present invention are not limited to the effects described above, and should be understood to include all effects that can be inferred from the configuration of the invention described in the detailed description of the invention or the claims. Brief explanation of the drawing
[0025] FIG. 1 is a flowchart schematically illustrating a method for exfoliating low-dimensional nanomaterials according to one embodiment of the present invention. FIG. 2 is a flowchart schematically illustrating a method for manufacturing a liquid crystal-low-dimensional nanomaterial composite according to one embodiment of the present invention. FIG. 3 is a conceptual diagram showing a peeling method according to an embodiment of the present invention. Figure 4 is a diagram showing the liquid crystal orientation according to the phase transition temperature of a liquid crystal material. Figure 5 is a diagram showing the change in peeling concentration obtained by varying the mixing temperature of the peeling method according to one embodiment of the present invention. Figure 6 is a diagram showing sample images of a two-dimensional MoS2 solution exfoliated at different temperatures. Figure 7 is a diagram showing the dispersion stability of a two-dimensional MoS2-liquid crystal material solution. Figure 8 is a diagram showing the two-dimensional material size according to the mixing temperature. Figure 9 is an image showing a liquid crystal-low-dimensional nanomaterial composite according to the mixing temperature. Figure 10 is a diagram showing the average size of two-dimensional material particles according to the mixing temperature. Figure 11 is a diagram showing a TEM image of exfoliated two-dimensional MoS2. Figure 12 is a diagram showing the WAXS (wide-angle X-ray scattering) analysis results of a two-dimensional MoS2-liquid crystal composite. Figure 13 is a diagram showing the DSC analysis results of a two-dimensional MoS2-liquid crystal composite. Figure 14 is an image showing an exfoliation / dispersion solution using liquid crystal materials of WS2, h-BN, TiC, graphene, and carbon nanotubes (CNT). Figure 15 is a diagram showing a TEM image of a solution formed through a peeling method according to an embodiment of the present invention of hexagonal boron nitride (h-BN). Figure 16 is a diagram showing a TEM image of a solution formed through an exfoliation method according to an embodiment of the present invention of graphene. FIG. 17 is a diagram showing a TEM image of a solution formed through a peeling method according to an embodiment of the present invention of WS2. Figure 18 is a diagram showing a TEM image of a solution formed through a peeling method which is an embodiment of the present invention of TiC. Figure 19 is a diagram showing the average size of a two-dimensional material measured through dynamic light scattering analysis. Figure 20 is a diagram showing the results of concentration analysis of a two-dimensional material through thermogravimetric analysis (TGA). Figure 21 is a diagram showing the results of the concentration analysis of MoS2 solution according to the solvent. Figure 22 is a diagram showing the results of the concentration analysis of WS2 solution according to the solvent. Figure 23 is a diagram showing the results of the concentration analysis of h-BN solution according to the solvent. Figure 24 is a diagram showing the results of the concentration analysis of a graphene solution according to the solvent. Figure 25 is a diagram showing the results of the concentration analysis of the TiC solution according to the solvent. Specific details for implementing the invention
[0026] The present invention will be described below with reference to the attached drawings. However, the present invention may be implemented in various different forms and is therefore not limited to the embodiments described herein. Furthermore, in order to clearly explain the present invention in the drawings, parts unrelated to the explanation have been omitted, and similar parts throughout the specification have been given similar reference numerals.
[0027] Throughout the specification, when it is stated that a part is "connected (connected, in contact, combined)" with another part, this includes not only cases where they are "directly connected," but also cases where they are "indirectly connected" with other members interposed between them. Furthermore, when it is stated that a part "includes" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but rather allows for the inclusion of additional components.
[0028] The terms used herein are merely for describing specific embodiments and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as “comprising” or “having” are intended to indicate the presence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0029] Embodiments of the present invention will be described in detail below with reference to the attached drawings.
[0031] A method for exfoliating low-dimensional nanomaterials according to one embodiment of the present invention is described.
[0032] FIG. 1 is a flowchart schematically illustrating a method for exfoliating low-dimensional nanomaterials according to one embodiment of the present invention.
[0033] Although there are various approaches to exfoliating existing low-dimensional nanomaterials from bulk to thin layers, the most representative method, solution exfoliation, requires harsh conditions such as high voltage, high vacuum, and strong base conditions. Furthermore, since it is difficult to completely remove residual metal ions, the final product contains ionic impurities. In addition, in the case of MoS2, it is exfoliated into an unstable 1T (conductor) phase rather than a stable 2H (semiconductor) phase.
[0034] Additionally, the solution-phase exfoliation method involves adding a dispersant to disperse the exfoliated lower-dimensional material, but toxic solvents with a boiling point of 200°C or higher are frequently used, and residual dispersant also needs to be separated as an impurity.
[0035] Accordingly, the present invention presents a method for exfoliating low-dimensional nanomaterials using a liquid crystal material as an exfoliating agent / dispersing agent to solve the aforementioned problems.
[0036] Specifically, a method for exfoliating a low-dimensional nanomaterial according to one embodiment of the present invention comprises the steps of: mixing a low-dimensional nanomaterial bulk powder with a liquid crystal material to form a mixture as shown in FIG. 1 (S100); heating the mixture under a temperature condition of 70°C to 150°C (S200); adding a solvent to the mixture to form a solution (S300); and applying ultrasound to the solution (S400).
[0038] First, a step (S100) of forming a mixture by mixing a low-dimensional nanomaterial bulk powder with a liquid crystal material is described.
[0039] In the present invention, the low-dimensional nanomaterial refers to a one-dimensional or two-dimensional nanomaterial, and for example, the low-dimensional nanomaterial may be graphene, carbon nanotubes, transition metal dichalcogenides, TiC, or h-BN (hexagonal boron nitride).
[0040] In particular, the above dichalcogenide compounds (2D transition metal dichalcogenides, 2D TMDs) have diverse crystal structures and exhibit different physical, chemical, and optical properties depending on the phase, so they are used as semiconductor materials.
[0041] Specifically, the dichalcogen compound may be any one selected from the group consisting of MoS2, MoSe2, MoTe2, WS2, WSe2, WTe2, TaS2, TaSe2, TiS2, TiSe2, HfS2, HfSe2, SnS2, SnSe2, GeS2, GeSe2, GaS2, GaSe2, ZrS2, ZrSe2, Bi2S3, Bi2Se3, and Bi2Te3.
[0042] In the present invention, the liquid crystal material refers to a liquid crystal molecule having a liquid crystal phase. The present invention utilizes the liquid crystal molecule as a stripping agent / dispersing agent to strip low-dimensional nanomaterials.
[0043] At this time, the liquid crystal material is a reactive mesogen (RM) containing a benzoate functional group. According to one example, the liquid crystal material may be a nematic liquid crystal comprising any one selected from the group consisting of RM257 (2-Methyl-1,4-phenylene bis(4-(3-(acryloyloxy)propoxy)benzonate)), RM23 (4-(6-Acryloyloxyhexyloxy)-benzoesure (4-cyanophenylester)), RM105 (4-[[6-[(1-oxo-2-propenyl)oxy]hexyl]oxy]-, 4-methoxyphenylestere, LC242: 4-[[[4-1-Oxo-2-propenly]oxy]butoxy]carbonyl]oxy]benzoic acid 2-methyl-1,4-phenylene ester), R6M (1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene), but is not limited thereto. No, it includes all reactive mesogens containing benzoate functional groups.
[0044] In this case, the liquid crystal material may have acrylate terminal groups and be capable of polymerization into a polymer. In this case, low-dimensional nanomaterials can be exfoliated and dispersed using a monomer-form liquid crystal material, and then polymerized into a polymer; thus, unlike conventional liquid exfoliation methods, this method has the characteristic of being applicable in various fields.
[0045] In addition, in this step (S100), in order to exfoliate the previously described low-dimensional nanomaterial, a bulk powder of the low-dimensional nanomaterial is mixed with the liquid crystal material to form a mixture.
[0046] At this time, preferably, before mixing the low-dimensional nanomaterial bulk powder with the liquid crystal material in step S100, a step of drying the powder (S110); and a step of physically grinding the powder (S120) may be additionally performed.
[0047] The step of drying the powder (S110) is a step of removing residual moisture in the bulk powder, and, for example, as in the embodiment to be described later, the powder can be dried in an oven at 100°C for 1 hour.
[0048] The step of physically grinding the powder (S120) is performed for the effective exfoliation of the bulk powder, and a grinder or the like may be used. By physically grinding the powder, there is an advantage in that the exfoliation of low-dimensional nanomaterials can be carried out efficiently.
[0049] In addition, during the process of mixing the above-mentioned low-dimensional nano bulk powder with the above-mentioned liquid crystal material, stirring can be performed using a vortex mixer or the like.
[0051] Next, a step (S200) of heat-treating the mixture under temperature conditions of 70°C to 150°C is described.
[0052] This step corresponds to the step of heating a mixture of low-dimensional nanomaterials and liquid crystal materials at a predetermined temperature.
[0053] According to one example, the above-mentioned predetermined temperature may be 70°C to 150°C, preferably 125°C to 140°C, and most preferably 130°C. According to the present invention, the above-mentioned temperature condition is a very important variable in exfoliation using a liquid crystal material of low-dimensional nanomaterial. Since the orientation region of the liquid crystal decreases and mobility increases around the phase transition temperature of the liquid crystal material, a clear difference occurs in the concentration range of the solution after exfoliation. Therefore, since the concentration of the solution after exfoliation may be very low in a temperature range below 70°C, a temperature range of 70°C or higher is appropriate.
[0054] At this time, the heat treatment means may be performed, for example, in an oil bath, but is not limited thereto.
[0055] According to one example, the heat treatment can be performed for 6 to 24 hours under the temperature range described above.
[0057] Next, the step of adding a solvent to the mixture to form a solution (S300) and the step of applying ultrasound to the solution (S400) will be described.
[0058] In the step of forming the solution (S300), the solvent is a polar organic solvent that can effectively dissolve the liquid crystal, and may be, for example, tetrahydrofuran or N-methylpyrrolidone, but is not limited thereto.
[0059] According to one example, the solvent may be added at a concentration of 5 mg / ml to 20 mg / ml.
[0060] In the step of applying ultrasound (S400), ultrasound is applied to the solution in which a solvent has been added to the mixture to perform solution-phase exfoliation and dispersion.
[0061] According to one example, the time for applying the ultrasound may be 6 to 24 hours, but is not limited thereto, and may be performed for a suitable time for solution-phase exfoliation and dispersion to occur.
[0063] Next, a method for manufacturing a liquid crystal-low-dimensional nanomaterial composite according to another embodiment of the present invention will be described.
[0064] FIG. 2 is a flowchart schematically illustrating a method for manufacturing a liquid crystal-low-dimensional nanomaterial composite according to one embodiment of the present invention.
[0065] A manufacturing method according to an embodiment of the present invention relates to a method for manufacturing a composite comprising a low-dimensional nanomaterial exfoliated through the low-dimensional nanomaterial exfoliation method described above, and is characterized by comprising: a step of separating a low-dimensional nanomaterial bulk powder from the solution (S500) after the step of applying ultrasound to the solution in the exfoliation method; and a step of drying the solution (S600).
[0066] At this time, the above separation can be performed using centrifugation, and by separating the bulk powder contained in the solution from the solution and drying the solvent of the solution from which the bulk powder has been separated, a composite in which low-dimensional nanomaterials exfoliated on a liquid crystal are dispersed can finally be obtained.
[0067] The obtained composite differs from conventional dispersants because it possesses a very strong advantage of being able to align low-dimensional nanomaterials in a specific direction by utilizing the property of liquid crystals to align under electric / magnetic / mechanical stress.
[0068] The present invention will be explained in more detail below through manufacturing examples, comparative examples, and experimental examples. However, the present invention is not limited to the following manufacturing examples and experimental examples.
[0070] Preparation Example 1: MoS 2 - Preparation of liquid crystal material solutions and complexes
[0071] FIG. 3 is a conceptual diagram showing a peeling method according to an embodiment of the present invention.
[0072] MoS2 bulk powder was heated in a 100°C oven for 1 hour to remove residual moisture. The dried bulk powder was physically ground using a mortar for 30 minutes, then liquid crystal material RM 257 was added and mixed using a vortex mixer, and left in an oil bath for 24 hours.
[0073] 10 mg / ml of solvent was added to the above mixture, and solution-phase exfoliation / dispersion was carried out using ultrasound for 6-24 hours. After separating the bulk powder from the solution by centrifugation, a MoS2 liquid crystal material solution and a dried composite thereof were obtained.
[0075] Experimental Example 1: Analysis of Changes in Peeling Concentration According to Mixing Temperature
[0076] Figure 4 is a diagram showing the liquid crystal orientation according to the phase transition temperature of a liquid crystal material.
[0077] Figure 5 is a diagram showing the change in peeling concentration obtained by varying the mixing temperature of the peeling method according to one embodiment of the present invention.
[0078] As a result of mixing the bulk MoS2 liquid crystal material at 130°C for 24 hours and then proceeding with exfoliation, it can be seen that the highest concentration is obtained as shown in Fig. 5 above. In particular, it can be confirmed in Fig. 5 above that a clear change in concentration appears around the phase transition temperature (Tn, Ti) of the liquid crystal, and this is because, as shown in Fig. 4 above, the orientation field of the liquid crystal decreases and mobility increases as the temperature increases.
[0079] Figure 6 is a diagram showing sample images of a two-dimensional MoS2 solution exfoliated at different temperatures.
[0080] As shown in Figure 6 above, when bulk MoS2 is exfoliated into two-dimensional MoS2, it appears green.
[0082] Experimental Example 2: Variance Stability Analysis
[0083] The dispersion stability of exfoliated 2D MoS2 was analyzed using UV-vis analysis.
[0084] Figure 7 is a diagram showing the dispersion stability of a two-dimensional MoS2-liquid crystal material solution.
[0085] As shown in Figure 7 above, consequently, no restacking phenomenon caused by van der Waals forces of 2D MoS2 occurred, and excellent dispersion stability was shown for more than 200 days at a low temperature of 4℃.
[0087] Experimental Example 3: Analysis of Two-Dimensional Material Size According to Mixing Temperature
[0088] The size of 2D MoS2 under different temperature conditions was inferred through UV-vis spectroscopy.
[0089] Figure 8 is a diagram showing the two-dimensional material size according to the mixing temperature.
[0090] Figure 9 is an image showing a liquid crystal-low-dimensional nanomaterial composite according to the mixing temperature.
[0091] As the two-dimensional peak of UV-vis in Fig. 8 slopes upward to the right, the size and thickness of the two-dimensional MoS2 increase.
[0092] In addition, the powder at a low mixing temperature exhibits a dark color without green due to the thick thickness of the two-dimensional MoS2. As shown in Figure 9 above, it can be seen that the composite prepared at a mixing temperature of 130°C, which exhibits the highest concentration, has a dark and deep color due to the very high concentration of the two-dimensional MoS2.
[0093] In addition, the average size of the particles was measured through dynamic light scattering (DLS) analysis.
[0094] Figure 10 is a diagram showing the average size of two-dimensional material particles according to the mixing temperature.
[0095] The result of the above Figure 10 is as shown in Table 1 below.
[0096] MoS 2 (Mixing Temperature) Z-average (nm) PDI 70 285.7 0.105 90 257 0.141 110 197.8 0.191 130 163.4 0.218
[0097] As shown in Figure 10 and Table 1 above, it can be seen that the average particle size of 2D MoS2 differs by more than 100 nm depending on the reaction temperature, and it can be seen that it has a generally uniform particle size with a PDI value of 0.1 to 0.2.
[0099] Experimental Example 4: Morphology Analysis
[0100] Figure 11 is a diagram showing a TEM image of exfoliated two-dimensional MoS2.
[0101] As shown in Figure 11 above, the exfoliated MoS2 was observed to be a two-dimensional MoS2 with generally two or more layers, and it can be seen that exfoliation occurred effectively and re-aggregation did not occur.
[0102] Figure 12 is a diagram showing the WAXS (wide-angle X-ray scattering) analysis results of a two-dimensional MoS2-liquid crystal composite.
[0103] As shown in Figure 12 above, it can be confirmed that the two-dimensional peak of bulk MoS2 does not appear within the composite. Therefore, even though the color of the composite is dark, it can be seen that the exfoliated two-dimensional MoS2 is uniformly mixed into the liquid crystal material without re-aggregation.
[0105] Experimental Example 5: Analysis of Mixing Uniformity
[0106] To analyze the mixing uniformity of the two-dimensional material exfoliated within the composite, DSC (differential scanning calorimetry) analysis was performed.
[0107] Figure 13 is a diagram showing the DSC analysis results of a two-dimensional MoS2-liquid crystal composite.
[0108] As shown in Figure 13 above, it can be seen that the isotropic phase transition temperature in the nematic changes significantly as the concentration of 2D MoS2 increases, and the uniformly distributed 2D MoS2 changes the thermal properties of the composite.
[0110] Experimental Example 6: In the case of other two-dimensional materials
[0111] Figure 14 is an image showing an exfoliation / dispersion solution using liquid crystal materials of WS2, h-BN, TiC, graphene, and carbon nanotubes (CNT).
[0112] Figure 15 is a diagram showing a TEM image of a solution formed through a peeling method according to an embodiment of the present invention of hexagonal boron nitride (h-BN).
[0113] Figure 16 is a diagram showing a TEM image of a solution formed through an exfoliation method according to an embodiment of the present invention of graphene.
[0114] FIG. 17 is a diagram showing a TEM image of a solution formed through a peeling method according to an embodiment of the present invention of WS2.
[0115] Figure 18 is a diagram showing a TEM image of a solution formed through a peeling method which is an embodiment of the present invention of TiC.
[0116] As shown in FIGS. 14 to 18 above, it was confirmed that other 1- and 2-dimensional low-dimensional materials can also achieve exfoliation and dispersion stability. In particular, it was confirmed that 1-dimensional carbon nanotubes are also uniformly dispersed in solution.
[0117] Figure 19 is a diagram showing the average size of a two-dimensional material measured through dynamic light scattering analysis.
[0118] The results of the above Figure 19 are as shown in Table 2 below.
[0119] 2D Materials Z-average (nm) PDI MoS2 163.4 0.218 WS2 166.9 0.214 Graphene 224.5 0.315 h-BN 166.1 0.186 MXene 214 0.1036
[0120] As shown in Figure 19 and Table 2 above, the size of the exfoliated two-dimensional material is approximately 160 to 224 nm on average, and it can be confirmed that there is a generally uniform distribution of particle sizes.
[0121] Figure 20 is a diagram showing the results of concentration analysis of a two-dimensional material through thermogravimetric analysis (TGA).
[0122] Figure 21 is a diagram showing the results of the concentration analysis of MoS2 solution according to the solvent.
[0123] Figure 22 is a diagram showing the results of the concentration analysis of WS2 solution according to the solvent.
[0124] Figure 23 is a diagram showing the results of the concentration analysis of h-BN solution according to the solvent.
[0125] Figure 24 is a diagram showing the results of the concentration analysis of a graphene solution according to the solvent.
[0126] Figure 25 is a diagram showing the results of the concentration analysis of the TiC solution according to the solvent.
[0127] For example, if X is the weight ratio (wt%) of MoS2 in the complex and 1-X is the weight ratio (wt%) of the liquid crystal material in the complex, then in Figure 20 above, the formula X*8.9% + (1-X) * 90.2% = 78.5% is satisfied. Thus, the value of X can be calculated. By dividing X by the volume of the resulting solution, the concentration in the solution phase can be calculated. For example, in the case of MoS2, the value of X is 14.4 (mass% in the complex powder), and since the complex solution is 20 ml, the concentration in the solution phase is 7.2 mg / ml.
[0128] 2D Materials Concentration (mg / ml) Yield (%) MoS2 7.2 72 WS2 7.8 78 TiC 1.95 19.5 h-BN 6.5 65 graphene 2.4 24
[0129] Therefore, using the results of Figures 21 to 25 above, the mass ratio of the two-dimensional material in the complex can be determined.
[0131] According to an embodiment of the present invention, there is no need for a nitrogen atmosphere or vacuum conditions required in conventional processes, high-concentration peeling is possible even under atmospheric conditions, and a method is provided to have a simplified process by reducing the conventional two-step process, which involves peeling and dispersion using a liquid crystal material as a peeling agent / dispersing agent, into a one-step process in which peeling and dispersion are possible simultaneously.
[0132] Specifically, due to the simplified process, economic feasibility is ensured, mass production becomes possible, nanomaterials can be dispersed at a high concentration on the liquid crystal, and a dispersion solution with excellent dispersion stability can be obtained.
[0133] Furthermore, according to an embodiment of the present invention, the liquid crystal-low-dimensional nanomaterial composite prepared by drying the solution is expected to possess anisotropic mechanical, optical, and electrical properties because the liquid crystals are aligned in a specific direction by an electric field, magnetic field, or mechanical stress. Therefore, the prepared composite has the effect of being usable in various applications, such as high-strength composite materials, heat dissipation materials for thermal control, polarizing films for light control, electronic devices, and energy devices.
[0134] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical spirit or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form.
[0135] The scope of the present invention is defined by the claims set forth below, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.
Claims
Claim 1 A method for exfoliating a low-dimensional nanomaterial, comprising: a step of mixing a low-dimensional nanomaterial bulk powder with a liquid crystal material to form a mixture; a step of heating the mixture under atmospheric conditions at a temperature of 70°C to 150°C; a step of adding a solvent to the mixture to form a solution; and a step of applying ultrasound to the solution; wherein the step of forming the mixture is characterized by physically grinding the low-dimensional nanomaterial bulk powder and then mixing it with the liquid crystal material, and wherein the solvent is tetrahydrofuran or N-methylpyrrolidone. Claim 2 A method for exfoliating a low-dimensional nanomaterial according to claim 1, wherein the low-dimensional nanomaterial is graphene, carbon nanotubes, transition metal dichalcogenogen compounds, TiC, or hBN. Claim 3 A method for exfoliating a low-dimensional nanomaterial according to claim 1, wherein the liquid crystal material comprises a liquid crystal molecule containing a benzoate functional group. Claim 4 A method for exfoliating a low-dimensional nanomaterial according to claim 3, wherein the liquid crystal material comprises any one selected from the group consisting of 2-Methyl-1,4-phenylene bis(4-(3-(acryloyloxy)propoxy)benzonate); 4-(6-Acryloyloxyhexyloxy)-benzoesure (4-cyanophenylester); 4-[[6-[(1-oxo-2-propenyl)oxy]hexyl]oxy]-,4-methoxyphenylester; 4-[[[4-1-Oxo-2-propenly]oxy]butoxy]carbonyl]oxy]benzoic acid 2-methyl-1,4-phenylene ester; and 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene. Claim 5 delete Claim 6 A method for exfoliating low-dimensional nanomaterials according to claim 1, wherein the heat treatment step is performed for 6 to 24 hours. Claim 7 A method for exfoliating low-dimensional nanomaterials according to claim 1, wherein the heat treatment step is performed under temperature conditions of 125℃ to 140℃. Claim 8 delete Claim 9 A method for manufacturing a liquid crystal-low-dimensional nanomaterial composite comprising a low-dimensional nanomaterial exfoliated through the low-dimensional nanomaterial exfoliation method of claim 1, wherein, after the step of applying ultrasound to the solution, the method comprises: a step of separating a low-dimensional nanomaterial bulk powder from the solution; and a step of drying the solution. Claim 10 A liquid crystal-low-dimensional nanomaterial composite manufactured by the method for manufacturing a liquid crystal-low-dimensional nanomaterial composite of claim 9. Claim 11 A liquid crystal-low-dimensional nanomaterial composite according to claim 10, characterized by containing 10 to 20 wt% of a low-dimensional nanomaterial.
Citation Information
Patent Citations
Graphene based liquid crystal fiber and graphene based carbon fiber and method of manufacturing the same
KR1020200006275A
